Digital Inclusion among Community Older Adults in the Republic of Korea: Measuring Digital Skills and Health Consequences - Thet Htoo Pan; Myo Nyein Aung; Eun Woo Nam; Yuka Koyanagi; Hocheol Lee; Li Li; Myat Yadana Kyaw; Nadila Mulati; Saiyud Moolphate; Carol Ma Hok Ka; Jan A. G. M. van Dijk; Motoyuki Yuasa (MDPI AG, 2024)
Many older adults are increasingly embracing digital technology in the Republic of Korea. This study investigated the relationship between the digital skills of Korean older adults and their perceived health status and digital technology application for health promotion. This mixed-method study comprised a community survey of 434 older adults aged ≥65 in two cities in South Korea, followed by focus group interviews. Five types of digital skills, 'operational internet skills', 'information navigation skills', 'social skills', 'creative skills', and 'mobile skills', were measured using the LSE digital skill measurement instrument. Multivariable analysis identified the influence of digital skills on health-related outcomes. Among them, 'social skills' associated positively with self-rated health (β 0.37, 95%CI 0.08, 0.65). 'Information navigation skills' contributed positively to the use of digital technology and the internet for a healthy lifestyle in terms of improving eating habits (β 0.43, 95%CI 0.09, 0.77), accessing healthcare (β 0.53, 95%CI 0.21, 0.85), and accessing long-term care services (β 0.45, 95%CI 0.11, 0.79). Thematic analysis revealed that the study participants use Korean language-based resources such as Naver and Kakao Talk for social connection to promote a healthy lifestyle. This study concludes that encouraging initial and sustained use of the internet and enhancing digital skills among Korean older adults can promote active and healthy aging.